2020
DOI: 10.1177/0886260520959647
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Transitions in Intimate Partner Violence among Female Assigned at Birth Sexual and Gender Minority Youth

Abstract: Female-assigned at birth sexual and gender minorities (FAB SGM) are at elevated risk of experiencing intimate partner violence (IPV), yet little longitudinal research has been conducted with this population. In the current study, we attempted to understand how patterns of IPV victimization and perpetration, measured across a wide range of IPV behaviors (psychological, physical, sexual, cyber, and SGM-specific), changed over time for FAB SGM youth. Participants came from a longitudinal cohort study of FAB SGM l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Factors linked to victimization and perpetration include factors such as relationship fusion (Miller et al, 2001), lower self-esteem (Miller et al, 2001), higher levels of independence (Miller et al, 2001), hostility, aggression, and anger (Lewis et al, 2017; Pepper & Sand, 2015), instability and negative worldview (Pepper & Sand, 2015), and alcohol use (Lewis et al, 2017). Using longitudinal latent class analysis of 433 AFAB SGM individuals, Swann et al (2020) found that, over time, participants were more likely to transition to a “less severe” IPV class except when they maintained the same romantic partner across waves. The authors suggest that these findings point to IPV as being relationship specific in this population.…”
Section: Resultsmentioning
confidence: 99%
“…Factors linked to victimization and perpetration include factors such as relationship fusion (Miller et al, 2001), lower self-esteem (Miller et al, 2001), higher levels of independence (Miller et al, 2001), hostility, aggression, and anger (Lewis et al, 2017; Pepper & Sand, 2015), instability and negative worldview (Pepper & Sand, 2015), and alcohol use (Lewis et al, 2017). Using longitudinal latent class analysis of 433 AFAB SGM individuals, Swann et al (2020) found that, over time, participants were more likely to transition to a “less severe” IPV class except when they maintained the same romantic partner across waves. The authors suggest that these findings point to IPV as being relationship specific in this population.…”
Section: Resultsmentioning
confidence: 99%